Cultural adaptation in the era of climate change: An ethnographic study on the resilience of indigenous people at Chittagong Hill Tracts area in Bangladesh - Joydeb Garai; Hok Bun Ku (Natural Hazards Research)
Climate change has gained global recognition as one of the most urgent challenges in recent decades. Many indigenous people attempt to overcome great challenges in their lives by adhering to their cultural customs and traditional knowledge. This is especially true for those who live in isolated, hilly places and are dependent on natural resources. The aim of the paper is to critically investigate the cultural facets of indigenous people's adaptation to and resilience to climate change in the Chittagong Hill Tracts (CHT), namely in the Rangamati Sadar sub-districts of the Rangamati districts, in Bangladesh. This paper also examines how cultural components in indigenous community are changing and influencing the adaptation process in adverse situations. This study used a critical ethnography technique in conjunction with participant observation, in-depth interviews (N ​= ​55), and focus group discussions (N ​= ​5, 45 participants) during a one-year period (October 2019 to October 2020). According to the study's findings, climate change-related risks have significant adverse effects on indigenous people. However, they develop their strategies to adjust to the adverse environment, like building different kinds of houses, changing cultural customs, relying less on natural resources, and adhering to their indigenous knowledge. They also strengthen their prayers and ceremonial practices, which reinforce their communal ties and allow them to become more resilient against challenges in their community. The popular belief that Indigenous people are stupid, poor, and helpless while they wait for outside help is challenged by this study. It also refutes the discourse that indigenous strategies and knowledge are not undervalued and can be an effective instrument for the adaptation process and combating hazards.